2017
DOI: 10.3390/ijerph14090997
|View full text |Cite
|
Sign up to set email alerts
|

Delay Discounting as an Index of Sustainable Behavior: Devaluation of Future Air Quality and Implications for Public Health

Abstract: Poor air quality and resulting annual deaths represent significant public health concerns. Recently, rapid delay discounting (the devaluation of future outcomes) of air quality has been considered a potential barrier for engaging in long term, sustainable behaviors that might help to reduce emissions (e.g., reducing private car use, societal support for clean air initiatives). Delay discounting has been shown to be predictive of real world behavior outside of laboratory settings, and therefore may offer an imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 49 publications
(83 reference statements)
2
14
0
Order By: Relevance
“…This research combined with previous studies suggests that beyond frequent findings of increased happiness [e.g., (40)], improved attention [e.g., (32)], and reduced stress [e.g., (41)], exposure to natural as opposed to built environments also influences decision-making in the context of delay discounting, an important predictor of real world behavior [see also (47); for an example of increased cooperation with exposure to nature]. Reductions in delay discounting of air quality in real world situations will be necessary to address the effects of current and future emissions for our health and the health of our ecosystems (48). Importantly, exposure to natural as opposed to built environments may facilitate a beneficial and reciprocal interaction between humans and our ecosystems, with focus toward maximizing future ecosystem health, and therefore human health.…”
Section: Discussionmentioning
confidence: 99%
“…This research combined with previous studies suggests that beyond frequent findings of increased happiness [e.g., (40)], improved attention [e.g., (32)], and reduced stress [e.g., (41)], exposure to natural as opposed to built environments also influences decision-making in the context of delay discounting, an important predictor of real world behavior [see also (47); for an example of increased cooperation with exposure to nature]. Reductions in delay discounting of air quality in real world situations will be necessary to address the effects of current and future emissions for our health and the health of our ecosystems (48). Importantly, exposure to natural as opposed to built environments may facilitate a beneficial and reciprocal interaction between humans and our ecosystems, with focus toward maximizing future ecosystem health, and therefore human health.…”
Section: Discussionmentioning
confidence: 99%
“…Research on the discounting of environmental outcomes over longer time periods has not tended to use delays longer than 10 years (e.g., Meyer, 2013;Viscusi, Huber, & Bell, 2008a), although some researchers have used delays of up to 25 years (e.g., . Berry, Nickerson, and Odum (2017) stated that there is almost no research that uses the time-frames that environmental policies are designed for. Berry, Nickerson et al's own research on the discounting of air quality included a delay of 75 years, but more discounting research with long time frames is needed, especially considering that "the role of time is especially salient for environmental decisions, which have consequences that unfold over decades, centuries, or millennia" (Hardisty et al, 2012, p. 684).…”
Section: Temporal Discountingmentioning
confidence: 99%
“…Slightly more complex, two-parameter hyperbola-like functions, referred to elsewhere as hyperboloid functions (e.g., Berry, Nickerson, & Odum, 2017;Young, 2017), where an exponent, s, is added to the denominator, have also been described in relation to discounting data (Green & Myerson, 2004;Myerson & Green, 1995;Rachlin, 2006). In Myerson and Green's (1995) model:…”
Section: Hyperbolic Discountingmentioning
confidence: 99%
See 1 more Smart Citation
“…Within-subject analyses revealed that individuals who discounted gains steeply (“impulsively”) in one realm (e.g., monetary) also discounted gains steeply (“impulsively”) in other realms (e.g., air quality, health) and vice versa (see also Meyer, 2013 ; Johnson and Saunders, 2014 ; Kaplan et al, 2014 ; Richards and Green, 2015 for examples of environmental commodity discounting/support for long-term conservation goals). Extending this line of work Berry et al (2017a , b) showed that mechanisms similar to those driving decisions for monetary outcomes might also be driving decisions about air quality (and possibly other ecological outcomes). This line of research lends support to targeting the same underlying mechanisms to facilitate reduction of delay discounting (“impulsivity”) on a global scale (see Odum, 2011 ).…”
Section: Nature Exposure and Environmentally Relevant Decision-makingmentioning
confidence: 88%